Efektivitas Perda Kota Medan No. 2 Tahun 2024 mengenai Kewajiban Mempekerjakan Penyandang Disabilitas oleh Pemerintah Daerah Perspektif Siyāsah Dustūriyyah - Nurhidayah, Indah; Nas, Zulkifli (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the effectiveness of Medan City Regional Regulation No. 2 of 2024 regarding the obligation of the Regional Government to employ persons with disabilities from the perspective of siyāsah dustūriyyah. Medan City Regional Regulation Number 2 of 2024 stipulates the obligation for the Regional Government to employ at least 2% persons with disabilities from the total number of employees. This aims to realize inclusivity and equal employment opportunities for persons with disabilities within the governmental environment. This research is a non-doctrinal legal study. The data obtained are qualitative data using a juridical-empirical approach, namely by collecting data through interviews with employees with disabilities and related parties within government institutions. The data obtained were then analyzed qualitatively by linking them with the principles of siyāsah dustūriyyah. The results of the study indicate that the implementation of Medan City Regional Regulation Number 2 of 2024 has not been fully effective. This is due to burdensome administrative requirements, the lack of vocational programs and job training, as well as weak coordination among institutions. From the perspective of siyāsah dustūriyyah, this condition shows that the government's role in realizing public welfare and social justice for vulnerable groups has not been optimal. Therefore, further in-depth study is still needed to ensure that the results of this research are truly objective and in accordance with real conditions in the field, so that the analysis and conclusions drawn are accurate and accountable in line with the principles of public welfare and social justice.